Proposal of High-Temperature-Operation Tolerant SOI MOSFET and Preliminary Study on Device Performance Evaluation - Yasuhisa Omura (Active and Passive Electronic Components)
We propose a high-temperature-operation (HTOT) SOI MOSFET and show preliminary simulation results of its characteristics. It is demonstrated that HTOT SOI MOSFET operates safely at 700 K with no thermal instability because of its expanded effective bandgap. It is shown that its threshold voltage is higher than that of the conventional SOI MOSFET because its local thin Si regions offer an expanded effective band gap. It is shown that HTOT SOI MOSFET with 1-nm-thick local-thin Si regions is almost insensitive to temperature for 𝑇<700K (427 C). This confirms that HTOT SOI MOSFET is a promising device for future high-temperature applications.